The Effects of Seaport-Inland Port Dyads on Container Seaport Hinterland Delimitation - Gong, Xiaoxing; Lan, Jieyuan; Li, Yongfang; Zhang, Lingye (Promet - Traffic&Transportation, 2023)
The emerging seaport-inland port dyad contributes greatly to the development of seaport hinterlands. However, little research has examined its influence on container hinterland delimitation. This paper used an improved radiation model to study the effects of seaport-inland port dyads on the container seaport hinterland delimitation in the context of a Chinese multi-port system. The radiation of each seaport was estimated to track changes in the seaport superior hinterlands and hinterland ratings and discover the patterns of the effects. The results show that the formation of dyads expands the scope of superior hinterlands and improves the hinterland ratings of seaports. The provinces close to inland ports and far from seaports were significantly affected and the same inland port influenced seaports differently. These results demonstrate that establishing a seaport-inland port dyad is a good way to compete with other seaports for larger market shares. These different effects can serve as a guideline for seaport authorities to choose suitable dyads to achieve their hinterland targets.